The Impact of Negative Environmental Events on Corporate Stock Returns - Wang, Ye (2012)
This paper examines the common stock market response to the negative environmental events using event study methodology. I consider a sample of 70 harmful events in oil & gas and energy industries from 2000 to 2011, including 12 chemical release accidents, 24 gas leaks and 34 oil spill events. The results indicate that the sudden harmful environmental events do generate negative abnormal returns over the event period. Shareholders of responsible firms suffer significantly negative abnormal returns (about 1.56% on average) in the following two days after the event date. In addition, the impact of firm distinct characteristics and event specific factors are analyzed in the cross- sectional analysis. The outcomes imply that only event type contributes to the abnormal returns. The influences of firm size, gearing ratio, toxic release and explosion are too minor to explain the observed abnormal returns.